More evidence for the therapeutic role of pramipexole in upper limb restlessness due to cervical disc pathology? - Yuluğ, Burak; Hanoğlu, Lütfü; Brandmeier, Sema (Bentham Science Publ Ltd, 2018)
Background: The causal link between upper limb restlessness and cervical disc prolapsus is still unclear, and the exact role of the spinal cord in the origination of limb restlessness is not yet completely understood. Methods: Here we have evaluated the therapeutic effect of pramipexole (0.5mg/kg) in a 47-year old male with cervical disc prolapsus who described restlessness in his upper limb and neck. Results: The patient felt significantly better, and his symptoms improved near to complete after five days when we initiated 0.5mg/day pramipexole treatment. Conclusion: In our present paper, we provide more evidence for the role of pramipexole (0.5mg/day) in limb restlessness which is associated with cervical disc herniation. In this context, we also have discussed the underlying pathophysiology which seems to be responsible for the restlessness symptoms of the patients.
WOS: 000442221000009
PubMed ID: 29493461
Keywords: Cervical Disc Herniation; Arm Restlessness; Sensorimotor; Spinal Hyperexcitability; Spinal Dopaminergic Tracts; Myelopathy